DECK AND SKATEBOARD - PARK, SANG HYEOK (2022)
The present invention relates to a deck for boards and a skateboard having the same, and more specifically, to a deck for boards and a skateboard having the same, wherein an elastic force reinforcing member made of shape memory alloy is interposed between a plurality of stacked panels in order to increase the elastic force of the deck for boards itself to allow a user to perform jumping techniques in an easier and higher manner. To this end, the deck for boards according to the present invention is composed of a plurality of stacked panels, wherein the elastic force reinforcing member made of shape memory alloy is interposed between the panels. The skateboard according to the present invention is characterized by: a deck composed of the plurality of stacked panels, wherein the elastic force reinforcing member made of shape memory alloy is interposed between the panels; and a wheel unit mounted on the lower surface of the deck. 본 발명은 보드용 데크 및 이를 구비한 스케이트보드에 관한 것으로, 적층되는 복수개의 패널 사이에 형상기억합금으로 이루어진 탄성력 강화부재를 개재하여 보드용 데크 자체의 탄성력을 증대시켜 점프 기술을 더욱 쉽고 높게 구사할 수 있게 하는 보드용 데크 및 이를 구비한 스케이트보드에 관한 것이다. 상기와 같은 목적을 달성하기 위하여, 본 발명에 따른 보드용 데크는, 복수개의 패널이 적층되어 이루어지되, 패널들 사이에 형상기억합금으로 이루어진 탄성력 강화부재가 개재되어 있는 것을 특징으로 하며, 본 발명에 따른 스케이트보드는, 복수개의 패널이 적층되어 이루어지되, 패널들 사이에 형상기억합금으로 이루어진 탄성력 강화부재가 개재되어 있는 데크; 상기 데크의 저면에 장착된 바퀴부;를 포함하는 것을 특징으로 한다.